High prevalence of infectious events in thrombotic thrombocytopenic purpura and genetic relationship with toll‐like receptor 9 polymorphisms: experience of the French Thrombotic Microangiopathies Reference Center. Issue 2 (27th May 2013) - Morgand, Marjolaine; Buffet, Marc; Busson, Marc; Loiseau, Pascale; Malot, Sandrine; Amokrane, Kahina; Fortier, Catherine; London, Jonathan; Bonmarchand, Guy; Wynckel, Alain; Provôt, François; Poullin, Pascale; et al.
<x xml:space="preserve">Abstract</x> Background Infectious events have been reported as major environmental triggers of thrombotic thrombocytopenic purpura (TTP). We detail here the potential association between infections and TTP. Study Design and Methods We recruited randomly and prospectively a cohort of 280 consecutive TTP patients during a 9‐year period. Features of infection were systematically recorded. Results Features consistent with an infectious event were observed in 114 patients (41%) at time of TTP diagnosis. Infectious agents were documented in 34 cases and were mainly Gram‐negative bacilli. At time of diagnosis infected patients more frequently had fever (p < 0.001). Infections at diagnosis did not impact prognosis and outcome. Thirty‐six percent of patients experienced an infectious event during hospitalization, which resulted in more exacerbation of TTP (p = 0.02). Infections were not overrepresented during treatment in patients who received steroids and/or rituximab. Further genetic analysis of toll‐like receptor (TLR)‐9 functionally relevant polymorphisms revealed that TLR‐9 +2848 G and TLR‐9 +1174 A genotypes were more frequent in TTP patients than in controls (p = 0.04 and p = 0.026, respectively) and more particularly in patients negative for the Class II human leukocyte antigen system susceptibility allele DRB1*11 (p = 0.001 and p = 0.002, respectively). Haplotypes estimation showed that 1174A‐2848G haplotype was significantly more frequent in TTP (p = 0.004), suggesting a primary role for this haplotype variation in conferring a predisposition for acquired TTP. Conclusion Infections should be considered as an aggravating factor during the course of TTP. Particular polymorphisms in TLR‐9 gene may represent risk factors for TTP.